Characteristics of services and educational programs in libraries serving problem-based curricula: a group self-study. - Watkins, M C (1993)
A group of librarians from institutions with formal problem-based learning (PBL) curricula tracks began meeting informally in 1989 to explore the common elements among libraries serving PBL curricula. In 1991, a self-study was undertaken to delineate library services in these schools and also to identify the mechanisms that enable libraries to respond directly to the PBL curriculum. This paper reports results of this self-study, including findings regarding services, collection access, library access, and, particularly, areas that facilitate the PBL process, such as availability of on-demand and tailored user education, end-user literature searching, and electronic mail. Formal and informal library instruction, both optional and required, is described. The self-study also identified structured and unstructured methods of student access to PBL curriculum resources, including bibliographies, formally defined reserve collections, and student and faculty resources. The many roles of the professional librarian within the PBL curriculum are described; librarians may serve as traditional service providers, as resource persons, as faculty, or as tutors or facilitators in PBL curriculum sessions.